Sistem Informasi Vaksinasi Hewan Peliharaan dan Ternak di Kabupaten Kepulauan Sangihe - Lolaroh, Stefanie M.E.; Sentinuwo, Steven R.; Karouw, Stanley D.S. (Universitas Sam Ratulangi, 2019)
Abstract — The growth rate of pets and livestock in Indonesia is increasing by days which has impacted remote areas especially in Sangihe Island District. The recapitulation results of BP4K, the number of pets (dogs) in Sangihe Island is keep increasing more than 1000 in 2 years. Pets and livestock have a close relation with vaccination, in Sangihe Islands BP4K is still giving information about vaccination manually so miscommunication often happened. Therefore, the Pet and Livestock Vaccination Information System in Sangihe Island District is made to facilitate the BP4K in Sangihe Islands to give information about vaccination. In making the Information System the author used Unified Software Development Process (USDP) as the method. Keywords — Animal; Information; Livestock; Pet; Sangihe; System; Vaccination. Abstrak — Angka pertumbuhan hewan di Indonesia kian meningkat, dan berdampak hingga di Kabupaten Kepulauan Sangihe. Dari hasil rekapan BP4K Bidang Peternakan, jumlah hewan peliharaan (anjing) di Kabupaten Kepulauan Sangihe meningkat sebanyak lebih dari 1000 ekor dalam kurun waktu 2 tahun. Hewan peliharaan maupun ternak pasti erat hubungannya dengan vaksinasi, di Kabupaten Kepulauan Sangihe sendiri BP4K masih menyampaikan informasi pemberian vaksinasi dengan cara manual sehingga kerap terjadi miskomunikasi. Oleh karena itu Sistem Informasi Vaksinasi Hewan Peliharaan dan Ternak di Kabupaten Kepulauan Sangihe dibangun untuk mempermudah BP4K Kabupaten Kepulauan Sangihe dalam menyampaikan informasi mengenai pemberian vaksinasi. Dalam membuat Sistem Informasi ini penulis menggunakan Metode Unified Software Development Process (USDP). Kata kunci — Hewan; Peliharaan; Sangihe; Sistem; Ternak; Vaksinasi.